Mechanical properties and microstructure of VPS and HVOF CoNiCrAlY coatings - Saeidi, S; Voisey, K.T.; McCartney, D.G. (Springer, 2011)
HVOF and VPS coatings were sprayed using a Praxair (CO-210-24) CoNiCrAlY powder. Free standing coatings underwent vacuum annealing at different temperatures for times of up to 840h. Feedstock powder, as-sprayed and annealed coatings were characterised by SEM, EDS and XRD. The hardness and Young’s modulus of as-sprayed and annealed HVOF and VPS coatings were measured, including determination of Young’s moduli of the individual phases via nanoindentation and measurement of Young’s moduli of coatings at temperatures up to 500°C. The Eshelby inclusion model was used to investigate the effect of microstructure on the coatings’ mechanical properties. The sensitivity of the mechanical properties to microstructural details was confirmed. Young’s modulus was constant to ~200°C then decreased with increasing measurement temperature. Annealing increased Young’s modulus due to a combination of decreased porosity and β volume fraction. Oxide stringers in the HVOF coating maintained its higher hardness than the VPS coating even after annealing.